PENGEMBANGAN MODEL PERMAINAN BOLA BASKET TAKI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN SISWA SEKOLAH DASAR KELAS ATAS DI KOTA GORONTALO (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
The Purpose of this research development was to produce a developing product of basket ball as teaching media of physical education, sport, and health for students of high-grade elementary school. In more specific goal, this research was hopely to raise instructional process of physical, sport, and health education, and to identify characteristic, specialty, and the limitation of learning model that was improved. This thesis is a research and development. The developing of the product of basket ball as teaching media of physical education, sport, and health for high-grade elementary school students, was done through several stages: draft designing of the product, validation of experts, few scale experiment, the first of revision, large scale experiment, the second revision (the last revision). The subject of this research were the student of high grade elementary from state elementary school (SDN) No. 33 Kota Selatan, SDN No. 96 Kota Utara, SDN No. 81 Kota Tengah. There were 218 students for subject of research. validation of experts was done by three experts and two physical education teachers. The few scale experiment was done to 28 students and the large scale experiment was done to 218 students. The data was collected by using questioner. The data consists of evaluation for product quality, suggestion for product improvement and student response to the model. Instrument validity test of psychomotor aspect shown by .564, cognitive aspect shown by .562, and affective aspect shown by .677. The correlate shows that totality instrument was valid. Instrument reliability test of psychomotor aspect shown by .657, cognitive aspect shown by .516, and affective aspect shown by .791. The correlate shows that totality instrument was reliable. The result of this research was a product of basket ball model as teaching media of physical education, sports and health. Based on the large scale experiment, it found if total score frequency of psychomotor aspect, cognitive aspect, affective aspect, shows that there are 94,50% of 218 score total students involved in good category, 5,50% of 218 score total students involved in average category, and no one score total students involved in lack category. The total score describing of basic competence attainment in instructional process of physical education, sport, and health through using taki basket. The Conclusion of this research was a product of basket ball model as teaching media of physical education, sports and health that can be use to raise fundamental skill of students, and can be use to raise students understanding of concept of cooperation, fair play, and honesty. Based on result of this research, the suggestion is the physical education elementary school teachers can use the product of basket ball model as physical education, sport, and health as teaching media for high grade elementary school students.